Incorporating the Hendricksons - Larry E. Ribstein (Washington University Journal of Law & Policy, 2011)
In this Essay, the author presents the differences between domestic and business partnerships and the potential problems that may arise in combining the two. It states that in both domestic and business association, standard forms are beneficial in the clarification of the relationships of the parties and in increasing opportunities. The author discusses the differences between the said partnerships, which include the manner which they are formed, management, and the fiduciary duties of their respective members.
Keywords: Domestic relations; Corporations; Conflict of laws; Interpersonal relations; Law & economics; Business associations; Family law; Family-owned businesses; Fiduciary duties